SOCIAL CONDITIONING OF GENDER ROLES THROUGH ADVERTISEMENTS IN INDIA - .R, Roshini; V, Rajasekaran. (International Journal of Psychosocial Rehabilitation, 2020)
The unfair treatment of women by the society is often justified by authoritative male gender in the name of familial duties and customary traditions, but is this injustice rational? This paper attempts to look into the role of mass media, specifically advertisements, in shaping gender roles. A few advertisements are critically analysed to bring out the gender biased portrayal of men and women in the advertisements and probes into the dangerous attitudes that it develops in the society due to this biased portrayal that is often very subtle.